THE MAIN FEATURES OF ESP TEACHING FOR STUDENTS OF ECONOMICS - Кириченко, Тетяна; Рідель, Тетяна (SWorldJournal, 2022)
In the context of globalization and international economic relations development, the demand of English language for specific purposes is growing. English language being recognized as an international language, provides the significant contribution into